The Zero Waste Catfish Product Innovation as an Empowerment Strategy Accompanied by Bunda KoJa Community Around Operational Area of PT Pertamina (Persero) Integrated Terminal Jakarta - Andri Akbar; Ryan Hendra; Anita Ervina; Rida Aini Rahmawati (Future Science)
Rawa Badak Selatan is one of some villages in Koja Subdistrict, North Jakarta that dominated by toddler parents with a lack of knowledge and economic prosperity about food nutrition. Corporate Social Responsibility (CSR) of PT. Pertamina Integrated Terminal Jakarta is carrying the SULE program as a strategy to empower toddlers mother by innovating catfish products, this program aims to increase productivity and improve the nutrition of toddlers. The data collecting method is descriptive and the implementation program was by the participatory method. The SULE programs include learning about catfish product innovation, management of catfish food production, and product marketing. The food product development also conducts the zero-waste production that provides more benefits, reduce waste handling activities, increasing productivity, overcome environment pollutant, and increase income and efficiency. Catfish product innovations from the catfish fillet are nuggets, shredded meat, and sticks. Catfish bones are processed into bone chips, tempeh chips, and fishbone biscuits. The SULE program had a positive impact because toddler mothers with bunda koja community could have additional income from catfish production and marketing. In the future, innovations of new catfish processed products will be developed into great socio-preneur that improve the economy of more other toddler mothers.